Catalytic Cooperativity, Nuclearity, and O2/H2O2 Specificity of Multi‐Copper(II) Complexes of Cyclen‐Tethered Cyclotriphosphazene Ligands in Aqueous Media. Issue 42 (7th September 2017) - Wang, Le; Ye, Yong; Lykourinou, Vasiliki; Yang, Junliang; Angerhofer, Alexander; Zhao, Yufen; Ming, Li‐June
Abstract : Three ligandsL1, L2, andL3 with 2, 4, and 6 1, 4, 7, 10‐tetraazacyclododecane (cyclen) moieties attached to a cyclotriphosphazene core, respectively, were synthesized, and oxidation activities of their Cu II complexes were investigated. Aerobic oxidation of catechol by these complexes follows an intramolecular dinuclear pathway with significant cooperativity (i.e., θ ≈ 1.5 out of a maximum of 2 for two potential substrate binding sites) and kinetic constants (i.e., k cat = 17.5 × 10 –3 s –1, K m = 2.8 mm, and quite remarkable catalytic specificity k cat / K m 12.5m –1  s –1 per di‐Cu center), while that by untethered Cu II –cyclen follows a bimolecular dinuclear pathway without noticeable cooperativity ( θ = 0.96) and fourfold lower k cat, despite their similar dinuclear mechanisms. The proximity of Cu II centers is suggested by EPR spectra and relaxations, showing a broad spectral component particularly in Cu6 L3 . Thermodynamic parameters also indicate the significance of multi‐Cu II sites in the oxidative catalysis. Air is a more specific oxidation agent for the representative complex Cu2 L1, showing 3.2‐fold higher catalytic specificity k cat / K m than H2 O2 toward a catechol substrate. The research provides further molecular basis for future design of O2 /H2 O2 ‐specific oxidation of multi‐domain Cu complexes. Abstract : Catechol oxidation by three Cu II complexes of 1, 4, 7, 10‐tetraaza‐cyclododecane (cyclen) attached to a cyclotriphosphazene core follows enzyme‐like saturation kinetics and an intramolecular dinuclear pathway with significant cooperativity ( θ ≈ 1.5 with a maximum of 2 for two binding sites), but not so for the untethered Cu II –cyclen with a lower k cat / K m .